Post‐transplant lymphoproliferative disorder in pediatric intestinal transplant recipients: A literature review. (10th May 2018) - Stanley, Kaitlin; Friehling, Erika; Ranganathan, Sarangarajan; Mazariegos, George; McAllister‐Lucas, Linda M.; Sindhi, Rakesh
Abstract: Intestinal transplantation is a successful treatment for children with intestinal failure, but has many potential complications. PTLD, a clinically and histologically diverse malignancy, occurs frequently after intestinal transplantation and can be fatal. The management of this disease is particularly challenging. The rejection‐prone intestinal allograft requires high levels of immunosuppression, a precondition for PTLD. While EBV infection clearly plays a role in disease pathogenesis, the relatively naïve immune system of children is another likely contributor. As a result, pediatric intestine recipients have a higher risk of developing PTLD than other solid organ recipients. Other risk factors for disease development such as molecular and genomic changes that precipitate malignant transformation are not fully understood, especially among children. Studies on adults have started to describe the molecular pathogenesis of PTLD, but the genomic landscape of the malignancy remains largely undefined in pediatric intestinal transplant patients. In this review, we describe what is known about PTLD in pediatric patients after intestinal transplant and highlight current knowledge gaps to better direct future investigations in the pediatric population.